2019
DOI: 10.1111/1750-3841.14833
|View full text |Cite
|
Sign up to set email alerts
|

Are Canned Beverages Industries Progressively Switching to Bisphenol AF?

Abstract: Seven bisphenols, endocrine‐disruptor chemicals, were analytically determined for risk assessment in 52 large‐consumption beverages collected from the Italian market. The analytes under examination were bisphenol A, bisphenol F, bisphenol E, bisphenol B, bisphenol AF, bisphenol A diglycidyl ether, and bisphenol M. The concentration levels of all bisphenols detected ranged from Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…The predominance of BADGE (77% water and 61% sediments) suggests that although BPA is still the most widely manufactured and used bisphenol in Italy, other analogues are being progressively utilized by industries and consequently in the human activities as an alternative. This is consistent with monitoring results in food and biological samples (Gonzalez et al, ,2019, 2020; Russo et al, 2019). A consideration of the assessment of the potential risk for species living in this lagoon should be made taking into account the results according to the Equation ().…”
Section: Resultssupporting
confidence: 91%
“…The predominance of BADGE (77% water and 61% sediments) suggests that although BPA is still the most widely manufactured and used bisphenol in Italy, other analogues are being progressively utilized by industries and consequently in the human activities as an alternative. This is consistent with monitoring results in food and biological samples (Gonzalez et al, ,2019, 2020; Russo et al, 2019). A consideration of the assessment of the potential risk for species living in this lagoon should be made taking into account the results according to the Equation ().…”
Section: Resultssupporting
confidence: 91%
“…However, imported canned foods may still be a relatively substantial route of exposure to BPA, and to its analogues (Gonzalez et al 2020;Russo et al 2019b). Moreover, exposure to BPA and other bisphenols might come from other food contact materials or packaging as well (European Food Safety Authority 2015; Liao et al 2011).…”
Section: Concentrations Of Bisphenols In Urinementioning
confidence: 99%
“…Since our questionnaire was not designed specifically to assess exposure from diet, interpretations of our results regarding food consumption should be handled with caution. Exposure to bisphenols through food most likely originates from the packaging of the food, such as cans and containers or wraps made of plastic or recycled paper, from which bisphenols may migrate into the foodstuffs (Gonzalez et al 2020;Liao et al 2011;Russo et al 2019b;Teeguarden et al 2011). Although diet is the major exposure route to BPA, these suspected specific exposure contributors (e.g.…”
Section: Determinants Of Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have found these BPA analogues in various matrices, e.g. indoor dust (Liao et al, 2012b), sediments (Liao et al, 2012d) and different foodstuffs (Grumetto et al, 2013;Liao and Kannan, 2013;Chen et al, 2016;Russo et al, 2019a;Russo et al, 2019b). Little is known about the potential toxicity of these BPA alternatives, but there are indications that they too could have endocrine-disrupting or other detrimental properties (Rochester and Bolden, 2015;Gramec Skledar and Peterlin Masic, 2016;Bjornsdotter et al, 2017;Pelch et al, 2019), illustrating the importance of monitoring the human exposure to these chemicals.…”
Section: Introductionmentioning
confidence: 99%